Beneficial effect of Amorphophallus paeoniifolius tuber on experimental ulcerative colitis in rats. (1st January 2017) - Dey, Yadu Nandan; Sharma, Garima; Wanjari, Manish M.; Kumar, Dharmendra; Lomash, Vinay; Jadhav, Ankush D.
Abstract: Context: The tuber of Amorphophallus paeoniifolius (Dennst.) Nicolson (Araceae), commonly called Suran or Jimmikand, has high medicinal value and is used ethnomedicinally for the treatment of different gastrointestinal and inflammatory disorders. Objective: The present study evaluated the effects of extracts of Amorphophallus paeoniifolius tubers on acetic acid-induced ulcerative colitis (UC) in rats. Materials and methods: Wistar rats were orally administered methanol extract (APME) or aqueous extract (APAE) (250 and 500 mg/kg) or standard drug, prednisolone (PRDS) (4 mg/kg) for 7 days. On 6th day of treatment, UC was induced by transrectal instillation of 4% acetic acid (AA) and after 48 h colitis was assessed by measuring colitis parameters, biochemical estimations and histology of colon. Results: APME or APAE pretreatment significantly ( p  < .05–.001) prevented AA-induced reduction in body weight and increase in colitis parameters viz. stool consistency, colon weight/length ratio and ulcer score, area and index. Extracts treatment attenuated ( p  < .001) increase in alkaline phosphatase and lactate dehydrogenase in serum and myeloperoxidase activity and cytokines in colon tissue due to AA administration. Extracts treatment prevented AA-induced elevation in lipid peroxidation and decline in activities of superoxide dismutase and catalase and reduced-glutathione content ( p  < .05–.001) along with histopathological alterations. PRDS also showed similar ameliorative effect on colitis. Discussion and conclusion: APME and APAE showed a preventive effect on UC, and ameliorated inflammation and oxidative damage in colon. The effects may be attributed to presence of phytochemicals, betulinic acid, β-sitosterol, and glucomannan. In conclusion, the tuber of Amorphophallus paeoniifolius exhibited an anticolitic effect through anti-inflammatory and antioxidant action.